2023
DOI: 10.1111/jcmm.17926
|View full text |Cite
|
Sign up to set email alerts
|

The rejuvenating influence of young plasma on aged intestine

Taha Ceylani,
Hikmet Taner Teker,
Seda Keskin
et al.

Abstract: This study aims to investigate the effects of plasma exchange on the biomolecular profiles and histology of ileum and colon tissues in young and aged Sprague–Dawley male rats. Fourier transform infrared (FTIR) spectroscopy, linear discriminant analysis and support vector machine (SVM) techniques were employed to analyse the lipid, protein, and nucleic acid indices in young and aged rats. Following the application of young plasma, aged rats demonstrated biomolecular profiles similar to those of their younger co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…These perturbations potentially disrupt intestinal function, necessitating interventions to foster regeneration. 18 , 24 , 31 Our findings demonstrate that both IF and SCD Probiotics can alleviate these adverse changes associated with aging, indicating their potential as therapeutic strategies. The intestinal epithelium's primary food source is short‐chain fatty acids (SCFAs), produced by bacterial fermentation of complex carbohydrates in the gut.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These perturbations potentially disrupt intestinal function, necessitating interventions to foster regeneration. 18 , 24 , 31 Our findings demonstrate that both IF and SCD Probiotics can alleviate these adverse changes associated with aging, indicating their potential as therapeutic strategies. The intestinal epithelium's primary food source is short‐chain fatty acids (SCFAs), produced by bacterial fermentation of complex carbohydrates in the gut.…”
Section: Discussionmentioning
confidence: 62%
“…Aging‐induced alterations in the ileum and colon tissues of rats, as observed in our study, manifested as increased epithelial shedding, decreased density of goblet and Paneth cells, heightened inflammation, and morphometric changes. These perturbations potentially disrupt intestinal function, necessitating interventions to foster regeneration 18,24,31 . Our findings demonstrate that both IF and SCD Probiotics can alleviate these adverse changes associated with aging, indicating their potential as therapeutic strategies.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…HPB has demonstrated its potential in preventing the age-related decline in pancreatic β-cell replication [ 50 ]. Furthermore, elderly rats that received young blood plasma exhibited a decrease in lymphocyte infiltration in the intestine [ 51 ]. In the case of adipose tissue, HPB has shown to alleviate senescence and inflammation in aging mice [ 52 ].…”
Section: Rejuvenating Effects Of Young Blood On Aging Organsmentioning
confidence: 99%
“…The study revealed rejuvenating effects on aged ileum and colon tissues, suggesting a therapeutic potential for intestinal aging. 14 …”
Section: Introductionmentioning
confidence: 99%